Low-potential solid-solid interfacial charging on layered polyaniline anode for high voltage pseudocapacitive intercalation Li-ion supercapacitors. (January 2023) - Liang, Jiaxing; Rawal, Aditya; Yu, Mengying; Xiao, Kefeng; Liu, Huabo; Jiang, Yu; Lennon, Alison; Wang, Da-Wei
Abstract: Lithium-ion supercapacitors (LISCs) have attracted increasing attention for its competitive energy and power capabilities compared with electric double layer capacitors and lithium-ion batteries. The working voltage of LISCs is the potential difference between the cathode and the anode and is oftentimes determined by the lower potential limit of the anode. Up to date, only carbon and MXene anodes can allow charge/discharge at low potentials. Here, we report electrochemically tuned layered polyaniline with solidified SEI nanochannels that promises as new type low potential anode for high voltage pseudocapacitive intercalation LISCs (PI-LISCs). We found that the tuned layered polyaniline attained high volumetric capacity of 196 mAh cm −3 at 25 mA g −1 at potentials as low as 0.01 V vs. Li/Li +, while allows the fabrication of a high voltage PI-LISC at 4.5 V with a high energy density of 100.5 Wh L −1 at 219.8 W L −1 and a high power density of 13.7 kW L −1 at 27.9 Wh L −1, as well as excellent capacity retention at 90.1 % after 10, 000 cycles. Our findings present a significant step forward to open up new opportunities of high energy and high power PI-LISCs. Graphical Abstract: Pseudocapacitive intercalation materials demonstrate battery-like high energy, capacitor-like high power and long lifespan as active materials in lithium-ion supercapacitors (LISCs). Here, a layered conducting polymer is applied as low potential anode with pseudocapacitive ion intercalation and solid-solid interfacial charging kinetics. Finally, a 4.5 V pseudocapacitive intercalation LISCs (PI-LISCs) based on layered polyaniline is developed with high voltage, superior volumetric performance, and excellent cycling stability. ga1 Highlights: A low-potential pseudocapacitive cation intercalation anode is designed for Li-ion supercapacitors. Solid-electrolyte interphase is constructed on the outer and inner surfaces of layered polyaniline (et-TALP). et-TALP stores energy via Li-ion intercalation and solid-solid interfacial charging. A 4.5 V pseudocapacitive intercalation Li-ion supercapacitor (PI-LISC) is configured. The as-obtained PI-LISC demonstrates superior volumetric performance and lifespan.